Comparison of the Mechanical Behaviour of Concrete Reinforced with Industrial Metal Fibres and Recycled Chips in Acidic Environments (Journal of Civil Engineering Researchers, 2025)
In recent years, most of the laboratory research on the comparison of the mechanical behaviour of reinforced concrete containing industrial metal fibres and recycled chips has been carried out abroad, and it is necessary to carry out special studies on reinforced concrete with domestic materials, so that we can produce a recycled reinforced concrete from metal waste and recycled chips that is resistant to acid attack and can be used in the construction industry. First we prepare the materials and fibres required for the test, then we design an optimal mixing plan in which industrial metal fibres and recycled chips are used in different percentages. The recycled chips are added to the concrete mix in such a way that the amount of chips we add reduces the amount of fine-grained sand, and the chips replace a small percentage of the sand. Concrete samples are then taken according to the mix design and tested after curing at a specified age. We compare concrete samples containing industrial metal fibres and recycled chips after exposure to an acidic environment with a concrete sample without fibres exposed to an acidic environment to understand how much the presence of fibres and chips in the concrete mix has increased the resistance of the concrete to acid.
Keywords: Mechanical behaviour; Reinforced concrete; Industrial metal fibres; Recycled chips; Acidic environment